Investigating subtitle translation of swear words in "Whiplash" - an audience movie reception study = Nghiên cứu về ảnh hưởng của việc dịch những từ ngữ thô tục trong phim “Whiplash” tới sự tiếp nhận của khán giả - Chu, Thị Hương Giang (2020)
The research investigated the effects of subtitle translation of swear words in the movie “Whiplash” on the reception of audience. Based on the hypothesis that “Audience’s opinions about swear word translation and about the movie depend on their English proficiency” two groups of viewers: one with high English competency and the other with little knowledge of the English language were asked to participate in the study. In order to achieve the objectives of the research, the researcher had two research questions along with two hypotheses, all of which have yielded useful information and findings presented in Chapter 4. Structured questionnaire and semi-structured interview were employed to collect data, probing into respondents’ opinions of swear words and the movie; meanwhile, content analysis was the main data analysis method. The findings indicated that swear words identification and the feelings about those words were different within and across the two surveyed groups. Moreover, the Vietnamese subtitled version of “Whiplash” was satisfactory and did not significantly alter the initial intention of the movie